PERANCANGAN DAN IMPLEMENTASI SISTEM PENGELOLAAN LAUNDRY ONLINE BERBASIS WEB - Edi Nurmansyah; Khoiriyah Namira Istiqa; Muhammad Muiduddin; Samin Arizal; Sifa Dwi Ahmad (Jurnal Riset Multidisiplin Edukasi, 2025)
Advances in information technology have driven digital transformation in various fields, including the laundry service sector. This study aims to design and implement an online laundry management system based on pickup and delivery to improve operational efficiency and customer convenience in utilizing laundry services. This system was developed using the Waterfall methodology approach, which includes the stages of requirements analysis, system design, implementation, and testing. The main features implemented include user registration, pickup and delivery service ordering, laundry status tracking, transaction management, and automatic financial report generation. Testing results show that the system is capable of optimizing laundry business processes by reducing manual recording errors and speeding up service processes. In addition, the implementation of this system can increase customer satisfaction through information transparency and easy online access to services. Thus, this online laundry management system is expected to be an effective solution in supporting the digitization of laundry services in the modern era.